Efficacy and tolerability of a sunscreen containing licochalcone A and L-carnitine as an adjunct to retinoids in the management of acne and post-acne pigmentation among Malaysian patients - How, Kang Nien; Ho, Wen Chung; Sundaran, Meroshini; Wan Ahmal Kammal, Wan Syazween Lyana; Lim, Poh Ying; Chew, Wilson (Informa UK Limited, 2023)
Purpose: We aim to evaluate the effectiveness and tolerability of a sunscreen formulation containing licochalcone A (LicA) and L-carnitine (LC) as an adjuvant to adapalene in the management of acne and post-acne pigmentation (PAH).